National socio-cultural values of the USA and its reflection in musical culture - Anufriev Evgeniy Alexandrovich, Anufrieva Natalia Ivanovna,; Pereverzeva Marina Viktorovna, Karsakova Irina Sergeevna, (Opción, 2019)
The aim of the article is to study the genre music system of the United States, its representatives and socio-cultural principles. The work presents an overview of the US musical culture formation process in the context of major socio-cultural principles via qualitative comparative analysis. As a result, the concept of the national principle in American music is broad and ambiguous, which is due to the unique features of the country's culture. In conclusion, musical culture is one of extremely complex formations, in which aesthetic, psychological, social, communicative and other directions intertwine.